Favorable impact of Nigella sativa seeds on lipid profile in type 2 diabetic patients - Huda Kaatabi; Abdullah O Bamosa; Fatma M Lebda; Abdulmohsen H Al Elq; Ali I Al-Sultan (Wolters Kluwer Medknow Publications, 2012)
Background and Aim: The atherogenic pattern of dyslipidemia associated with type 2 diabetes mellitus (DM) has been increasingly discussed. We have recently reported a hypoglycemic effect of Nigella sativa (NS) seeds in patients with type 2 DM. In this study we sought to assess the impact of NS seeds on lipid profile in type 2 diabetic patients. Patients and Method: A total of 94 patients with type 2 DM were recruited and divided into 3 dose groups. Capsules containing NS were administered orally in a dose of 1, 2, and 3 g/day for 12 weeks. All patients were subjected to measurement of total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-c), and high-density lipoprotein cholesterol (HDL-c) before treatment and 4, 8, and 12 weeks thereafter. Results: Patients receiving 1 g/day NS seeds for 12 weeks (group 1) showed nonsignificant changes in all the parameters except for a significant increase in HDL-c after 4 weeks of treatment. However, patients ingested 2 g/day NS displayed a significant decline in TC, TG, and LDL-c, and a significant elevation in HDL-c/LDL-c, compared with their baseline data and to group 1 patients. Increasing NS dose to 3 g/day failed to show any increase in the hypolipdemic effect produced by the 2 g/day dose. Conclusion: NS supplementation at a dose of 2 g/day for 12 weeks may improve the dyslipidemia associated with type 2 diabetic patients. Therefore, NS is a potential protective natural agent against atherosclerosis and cardiovascular complications in these patients.